The Influence of Service Quality on Consumer Purchase Decisions - Erlina Puspitaloka Mahadewi; Arnastya Iswara Sanantagraha (CV. Astina Mandiri, 2024)
This study aims to determine the effect of service quality on consumer purchasing decisions at Warung Makan Soto Madura in Ciputat, South Tangerang. The method used is explanatory research with a sample of 99 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study, the service quality variable obtained an average score of 3.42 with good criteria. The purchasing decision variable obtained an average score of 3.84 with good criteria. Service quality has a significant effect on purchasing decisions with the regression equation Y = 8.624 + 0.871X, and a correlation value of 0.770 or strong with a determination of 59.3%. Hypothesis testing obtained t count> t table or (11.699> 1.986) and a significance of 0.000 <0.05.